Grouper DNA barcoding studies in Indonesia: A short review - Nanda Muhammad Razi; Zainal A. Muchlisin; Siti Maulida; Mutia Ramadhaniaty; Firman M. Nur; Adrian Damora; Sumarni Laila Buang Manalu; Nur Fadli (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2021)
Indonesia is recognized as one of the territories that have the highest reef fish biodiversity in the world. One of the commercially valuable fish in this area is the groupers (locally name